Effects of pretreatment on properties of gelatin from perch (Lates Niloticus) skin - Hammed, Ademola Monsur; Jaswir, Irwandi; Mohd. Salleh, Hamzah; Alkahtani, Hassan (Taylor and Francis, 2014)
Fish gelatins obtained from perch fish skin pretreated with various solutions containing acetic acid, sodium hydroxide (NaOH) and sodium chloride (NaCl) were successfully characterized for their nanostructure pattern using field emission scanning electron microscopy. Each pretreatment transformed collagen to gelatin with fibril, zigzag cracks, straight rods, and cross-linked rods nanostructure patterns. Pretreatment solutions also affect the gel yield, gel strength, amino acid profile, and functional groups in perch gelatin as analyzed by Fourier transform infrared spectroscopy. Samples pretreated with NaCl, NaOH, and acetic acid solution showed the highest gel yield (22.84%) and gel strength (179.84 g). Fourier transform infrared spectra for perch gelatins also revealed weak C–N amide II and III bond stretches as well as weak C=O bond stretch.